Perancangan Pemberian Pakan Ikan Otomatis Berbasis Arduino Dengan Indikator SMS - Rifqi Andreyanto; Andre Mochammad Satrio; M. Mujirudin; Dwi Astuti Cahyasiwi (Prosiding Seminar Nasional Teknoka, 2019)
This paper discusses the fish feed which is done automatically with an arduino uno microcontroller. Giving is done by setting the time and status notifications via short messages or SMS as indicators to monitor remotely. Other indicators are LCD, LED, and Buzzer. Feeding method is carried out with a predetermined schedule in accordance with the development of fish weight. This automatic feed tool can detect that the feed has been used up by using an LDR sensor. The results showed that this automatic fish feed is able to accommodate feed in its container as much as 3kg as well as the expenditure of feed which has an error or error of 0%. Can detect feed depleted by the LDR sensor if the remaining fish feed remains as much as 20.5gram.